Previous injury is associated with heightened countermovement jump force-time asymmetries in professional soccer players - Hart, L. M.; Cohen, D. D.; Patterson, S. D.; Springham, M.; Reynolds, J.; Read, P. (Translational Sports Medicine, 2019)
Previous injury is associated with increased risk of future injury. Residual inter-limb deficits are a potential contributing factor leading to compensatory movement patterns on return to sport. The purpose of this study was to examine the effects of previous severe injury on bilateral ground reaction force asymmetries measured during a countermovement jump using a dual force platform. A total of 34 male professional soccer players (age 19 ± 2 years) were subdivided into two groups; previous severe injury (N = 17) or no severe injury (N = 17). Previously injured players showed significantly greater asymmetry in concentric phase variables (P < 0.05) with strong effect sizes (range = 0.99-1.35). These players also showed significantly elevated asymmetry in eccentric phase variables (P < 0.05) and medium to large effect sizes (range = 0.73-1.05), with the exception of eccentric deceleration impulse (P > 0.05; d = 0.33). There were no significant between-group differences in bilateral jump performance parameters (P > 0.05). These data indicate that despite being cleared to return to sport, participating in elite-level training, full competition and exhibiting no decrements in jump performance, significant inter-limb asymmetries persist in the concentric and eccentric phases of the CMJ.